Facies and Diagenetic Level of the Upper Cibulakan and Parigi Formation, in Randegan and Palimanan Area - Moeh. Ali Jambak; Ildrem Syafri; Vijaya Isnaniawardhani; Benyamin Benyamin; Hilarius Rodriguez (Geological Agency, 2015)
DOI:10.17014/ijog.2.3.157-166This research aims to determine the facies and diagenetic level of limestone of the Upper Cibulakan and Parigi Formations, and also aims to determine the structural correlation between surface and subsurface limestones. Based on thin section analyses taken from the core and outcrop samples, there are four types of lithofacies on the Upper Cibulakan Formation, i.e. mudstone-wackestone, wackestone-packstone, packstone-grainstone, and grainstone facies, and also four types of lithofacies on the Parigi Limestone Formation, i.e. mudstone-wackestone, wackestone-packstone, packstone-grainstone, and lower mudstone-wackestone facies. The analysis of surface and subsurface limestone facies of the Upper Cibulakan and Parigi Formations led to the knowledge of the proportionality and variation of the limestone characteristics on both positions. Limestone of the Upper Cibulakan Formation was deposited locally and discontinuously, whilst the Parigi Formation limestone was deposited evenly and continuously. The structural correlation between the surface and subsurface limestone indicates that these formations were uplifted/exposed due to a local force, likely caused by the intrusion of igneous rocks, as happened in the Kromong Complex. The presence of residual hydrocarbon on the surface of the limestone samples suggests the possibility of potential hydrocarbon trapped in the limestone beneath the surface.